2019
DOI: 10.1021/acs.est.8b06879
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Toxicological Evolution of Engineered Nanoparticles with Atmospherically Relevant Coatings

Abstract: The health impacts associated with engineered nanoparticles (ENPs) released into the atmosphere have not been adequately assessed. Such impacts could potentially arise from the toxicity associated with condensable atmospheric secondary organic material (SOM), or changes in the SOM composition induced by ENPs. Here, these possibilities are evaluated by investigating the oxidative and toxicological evolution of TiO 2 and SiO 2 nanoparticles which have been coated with SOM from the O 3 or OH initiated oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Epoxide has been identified as a surface product on SWCNT when treated with high concentration of ozone (Mawhinney et al, 2000;Yim and Johnson, 2009). Besides carboxylic acids, esters (Liu et al, 2015), ketones, lactone and anhydride species (Liu et al, 2010;Han et al, 2012b), epoxides have also been identified as the surface product during oxidation of SWCNTs in atmosphere-relevant condi-tions (Liu et al, 2015). On the other hand, graphene oxide is an important commercial product, which showed a strong oxidation potential as observed in this work.…”
Section: Conclusion and Atmospheric Implicationssupporting
confidence: 71%
See 1 more Smart Citation
“…Epoxide has been identified as a surface product on SWCNT when treated with high concentration of ozone (Mawhinney et al, 2000;Yim and Johnson, 2009). Besides carboxylic acids, esters (Liu et al, 2015), ketones, lactone and anhydride species (Liu et al, 2010;Han et al, 2012b), epoxides have also been identified as the surface product during oxidation of SWCNTs in atmosphere-relevant condi-tions (Liu et al, 2015). On the other hand, graphene oxide is an important commercial product, which showed a strong oxidation potential as observed in this work.…”
Section: Conclusion and Atmospheric Implicationssupporting
confidence: 71%
“…S1 in the Supplement. The diameters of primary particles were analyzed by ImageJ 1.41 software (Liu et al, 2010). The diameter of the primary carbon sphere for SB4A was 66 ± 17 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the SVOC products on dust can be oxidized by OH radicals to form less volatile HOM compounds, resulting in an increase of SOA yield. For example, the oxidation state (O to C ratio) of α-pinene SOA in the presence of TiO 2 particles was reported to be increased under UV irradiation, 61 which verified the oxidation of organic compounds on the dust surface. Therefore, the effects of photocatalytic oxidation of SVOC on the SOA yield are probably compensated by the formation of both less volatile HOM compounds and more volatile IVOCs.…”
Section: Resultsmentioning
confidence: 82%
“…Specifically, semiconductive metal oxides in dust particles can photocatalytically oxidize organic products on dust particles. Hygroscopic inorganic slats absorb water vapor and promote heterogeneous reactions of reactive oxygenated products, such as aldehydes, to form oligomeric products. For heterogeneous chemistry of organic products on dust particles, we propose three reaction mechanisms: (1) the formation of carboxylate salts by the reaction of alkaline carbonates with carboxylic acids (Section ); ,, (2) the photooxidation of the SVOC products partitioned on dust particles, leading to both highly oxidized multifunctional (HOM) compounds and intermediate VOCs (IVOCs) (Section ); , and (3) heterogeneous reactions of oxygenated products in dust-phase water layers (Section ). Figure summarizes the mechanistic role of mineral dust in SOA growth.…”
Section: Resultsmentioning
confidence: 99%
“…Different from most naturally occurring nano-objects, nanomaterials originating from anthropogenic sources can have substantial toxic effects on human health and the environment. 3,4 Two main categories belong to this material class, namely the manufactured nanomaterials and the incidental nano-objects generated in thermal treatment processes mainly in the form of carbon compounds. 5,6 The toxicity of manufactured nanomaterials is one of the most heavily researched topics in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%